Optogenetic control of gene expression in the cyanobacterium Synechococcus sp. PCC 7002 - Liam Forbes; Maria Papanatsiou; Anna Palombo; John M. Christie; Anna Amtmann (Frontiers in Bioengineering and Biotechnology)
Photosynthetic cyanobacteria can be utilised in biotechnology as environmentally sustainable cell factories to convert CO2 into a diverse range of biochemicals. However, a lack of molecular tools available for precise and dynamic control of gene expression hinders metabolic engineering and contributes to low product titres. Optogenetic tools enable light-regulated control of gene expression with high tunability and reversibility. To date, their application in cyanobacteria is limited and transferability between species remains unclear. In this study, we expressed the blue light-repressible YF1/FixJ and the green/red light-responsive CcaS/CcaR systems in Synechococcus sp. PCC 7002 and characterised their performance using GFP fluorescence assays and qRT-PCR. The YF1/FixJ system of non-cyanobacterial origin showed poor performance with a maximum dynamic range of 1.5-fold despite several steps to improve this. By contrast, the CcaS/CcaR system originating from the cyanobacterium Synechocystis sp. PCC 6803 responded well to light wavelengths and intensities, with a 6-fold increased protein fluorescence output observed after 30 min of green light. Monitoring GFP transcript levels allowed us to quantify the kinetics of transcriptional activation and deactivation and to test the effect of both multiple green/red and light/dark cycles on system performance. Finally, we increased CcaS/CcaR system activity under green light through targeted genetic modifications to the pCpcG2 output promoter. This study provides a detailed characterisation of the behaviour of the CcaS/CcaR system in Synechococcus sp. PCC 7002, as well as underlining the complexity of transferring optogenetic tools across species.